2019
DOI: 10.3390/su11216044
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Acylation of Levoglucosan Catalyzed by Candida Antarctica (CaLB) Lipase Immobilized on Epoxy Resin

Abstract: Every year, a large amount of residual agroindustrial waste has been generated and only around 10% is in fact reused. The development of new strategies for biomass valorization is important to add value to these commodities, since biomass is an excellent alternative feedstock to obtain chemicals of interest from renewable resources. The major compound of pyrolytic treatment of lignocellulosic biomass is levoglucosan (1,6-anhydroglucopyranose), an anhydro-sugar that can be transformed into glucose and is greatl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 24 publications
1
19
1
Order By: Relevance
“…However, no assay to detect the presence of diesters has been performed. Recently 131 As a result, all biocatalysts generated mostly monoesters, where N435 was more selective to produce lauric esters (99% at 50°C) and PSIM to produce oleic esters (97% at 55°C) while CaLB_epoxy was more selective to produce oleic esters of LG (83% at 55°C) ( Fig. 14).…”
Section: Applications Of Pure Lgmentioning
confidence: 97%
See 2 more Smart Citations
“…However, no assay to detect the presence of diesters has been performed. Recently 131 As a result, all biocatalysts generated mostly monoesters, where N435 was more selective to produce lauric esters (99% at 50°C) and PSIM to produce oleic esters (97% at 55°C) while CaLB_epoxy was more selective to produce oleic esters of LG (83% at 55°C) ( Fig. 14).…”
Section: Applications Of Pure Lgmentioning
confidence: 97%
“…These experiments clearly showed that there were marked differences between reactivities on C2 and C4 hydroxyl groups and also the type of binding and the support chosen for enzyme immobilization can influence the selectivity of the enzyme so that the hydroxyl groups can be selectively transesterified, since CaLB_epoxy and N435 have the same enzyme (CALB), but immobilized on different supports, generating different interactions between the enzyme and support and consequently different spatial conformations, revealing different preferences in the reaction under study. 131…”
Section: Applications Of Pure Lgmentioning
confidence: 99%
See 1 more Smart Citation
“…3.1.1.3) have received great prominence in recent years [ 17 ]. Although the natural reaction of this class of enzymes is the hydrolysis of triacylglycerols, lipases are also capable of catalyzing synthesis reactions by recognition a high range of substrates, showing activity in organic solvents, in addition to acting with high regio-, enantio-, and chemo selectivity, factors that, together with the absence of co-factors, make these enzymes highly attractive in several industrial segments [ 18 , 19 , 20 , 21 , 22 ]. However, the applications of lipases in industrial processes are often hindered due to their low long-term stability and gradual decrease of activity during storage, expensive and/or inefficient recovery, and subsequent reuse [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…3.1.1.3) have received great prominence in recent years [17]. Although the natural reaction of this class of enzymes is the hydrolysis of triacylglycerols, lipases are also capable of catalyzing synthesis reactions by recognition a high range of substrates, showing activity in organic solvents, in addition to acting with high regio-, enantio-and chemo selectivity, factors that, together with the absence of co-factors, make these enzymes highly attractive in several industrial segments [18][19][20][21][22]. However, the applications of lipases in industrial processes are often hindered due to their low long-term stability and gradual decrease of activity during storage, expensive and/or inefficient recovery and subsequent reuse [23].…”
Section: Introductionmentioning
confidence: 99%